Learning to walk in another's shoes. (March 2017) - Gehlbach, Hunter
Despite the enthusiasm around social-emotional learning, the vast number of skills, dispositions, and attitudes we hope to infuse into students will overwhelm even the most ambitious schools. However, a single core capacity underlies a great many social-emotional learning outcomes: social perspective taking. Recent research on this process of "reading" others — figuring out their thoughts, feelings, and motivations — suggests that we now know enough to teach this capacity to students. By helping youth engage in this process regularly as "detectives" rather than "judges" and providing them with feedback, a constellation of social-emotional learnings will blossom .